The Implementation of Tut Wuri Handayani Values at the Taman Muda Elementary School Jetis Yogyakarta - Sugiyanto, Sugiyanto; LN, Syamsu Yusuf; Supriatna, Mamat (Jurnal Prima Edukasia, 2023)
This research aims to examine the noble values contained in tut wuri handayani and its implementation in education, which holds meaning as an educator or pamong who plays a role in developing students' abilities through the influence of education by providing freedom in learning to find the meaning of life. The research approach used in this study was phenomenology. The research method employed was hermeneutic phenomenology, which focuses on life experiences and interpreting the "text" of life. Data collection techniques include library research and interviews. The data sources consisted of writings by Ki Hadjar Dewantara on the noble values of tut wuri handayani, interviews with Tamansiswa figures, and interviews with the school principal and pamong of Taman Muda Jetis Elementary School. Data analysis was conducted using Interpretative Phenomenological Analysis (IPA). The research findings indicate that the values contained in tut wuri handayani can be applied in educational institutions to shape students who are independent in their thinking, inner selves, and abilities by avoiding behaviors contrary to the rules and norms.